A compact UWB monopole antenna with penta band notched characteristics - Majed O. Al-Dwairi; Amjad Y. Hindi; Mohamed S. Soliman; Mohammad F. Aljafari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
A modified rectangular monopole ultra-wideband (UWB) antenna with penta notched frequency bands is presented. An inverted U shaped and slanted U-shaped on the radiating patch are inserted to achieve WiMAX and ARN bands rejection respectively, two mirrored summation Σ-shaped and four mirrored 5-shaped slots are inserted on the partial ground to achieve WLAN and X-band bands rejection respectively, finally rectangular shaped slot with partially open on the feed is inserted to achieve ITU-8 band rejection. The proposed antenna which was simulated has a compact size 30×35×1.6 m3. It is operated with impedance bandwidth 2.8-10.6 GHz at |S11| < −10 dB, that supported UWB bandwidth with filtering the five narrowbands that avoid the possible interference with them. The simulated resonant frequency for notched filters received 3.55, 4.55, 5.53, 7.45, 8.16 GHZ, for WiMAX, ARN, WLAN, X-Band, ITU-8 respectively. The proposed antenna is suitable for wireless communication such as mobile communication and internet of everything (IoE). Throughout this paper, CST-EM software package was used for the design implementation. Surface current distributions for all notched filters were investigated and shown that it is concentrated around the feeding point and the inserted notched slots proving that there is no radiation to the space due to maximum stored electromagnetic energy around each investigated notch slot, proving that the slots play a role of a quarter wavelength transformer which generates for each notched band, maximum gain, and radiation pattern are also investigated.